ІГРОВА ДІЯЛЬНІСТЬ УЧНІВ У ПРОЦЕСІ НАВЧАННЯ ТА ФОРМУВАННЯ ІННОВАЦІЙНОЇ ОСОБИСТОСТІ (Педагогіка вищої та середньої школи, 2007)
The didactic game plays a great role in the process of teaching in a primary school In didactic games the child watches, compares, classifies objects, carries out a simple analysis and synthesis and makes conclusions. Capable guidance of a didactic game presents the teaching material to junior pupils in such a way that it helps to form and develop their subjective vital activity.